Easy and Low-Cost Method for Synthesis of Carbon–Silica Composite from Vinasse and Study of Ibuprofen Removal - Yuvarat Ngernyen; Thitipong Siriketh; Kritsada Manyuen; Panta Thawngen; Wipha Rodtoem; Kritiyaporn Wannuea; Jesper T. N. Knijnenburg; Supattra Budsaereechai (C, 2022)
Vinasse was successfully utilized to synthesize carbon–silica composite with a low-cost silica source available in Thailand (sodium silicate, Na2SiO3) and most commonly used source, tetraethyl orthosilicate (TEOS). The composites were prepared by a simple one-step sol–gel process by varying the vinasse (as carbon source) to silica source (Na2SiO3 or TEOS) weight ratio. The resulting composites were characterized by N2 adsorption, moisture and ash contents, pH, pHpzc, bulk density, Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and scanning electron microscopy-energy dispersive X-ray analysis (SEM-EDX). The composites had highest surface area of 313 and 456 m2/g, with average mesopore diameters of 5.00 and 2.62 nm when using Na2SiO3 and TEOS as the silica sources, respectively. The adsorption of a non-steroidal anti-inflammatory drug, ibuprofen, was investigated. The contact time to reach equilibrium was 60 min for both composites. The adsorption kinetics were fitted by a pseudo-second-order model with the correlation coefficient R2 > 0.997. The adsorption isotherms were well described by the Langmuir model (R2 > 0.992), which indicates monolayer adsorption. The maximal adsorption capacities of the Na2SiO3- and TEOS-based composites were as high as 406 and 418 mg/g at pH 2, respectively. The research results indicate that vinasse and a low-cost silica source (Na2SiO3) show great potential to synthesize adsorbents through a simple method with high efficiency.